Monoterpenes: current knowledge on food source, metabolism, and health effects. Issue 10 (15th April 2023) - de Alvarenga, José Fernando Rinaldi; Genaro, Brunna; Costa, Bruna Lamesa; Purgatto, Eduardo; Manach, Claudine; Fiamoncini, Jarlei
Abstract: Monoterpenes, volatile metabolites produced by plants, are involved in the taste and aroma perception of fruits and vegetables and have been used for centuries in gastronomy, as food preservatives and for therapeutic purposes. Biological activities such as antimicrobial, analgesic and anti-inflammatory are well-established for some of these molecules. More recently, the ability of monoterpenes to regulate energy metabolism, and exert antidiabetic, anti-obesity and gut microbiota modulation activities have been described. Despite their promising health effects, the lack of reliable quantification of monoterpenes in food, hindered the investigation of their role as dietary bioactive compounds in epidemiological studies. Moreover, only few studies have documented the biotransformation of these compounds and identified the monoterpene metabolites with biological activity. This review presents up-to-date knowledge about the occurrence of monoterpenes in food, their bioavailability and potential role in the modulation of intermediate metabolism and inflammation, focusing on novel findings of molecular mechanisms, underlining research gaps and new avenues to be explored.